USING THE EFE MATRIX TO ASSESS THE FACTORS DETERMINING THE DEVELOPMENT OF ENERGY COOPERATIVES IN POLAND - Maryla Bieniek-Majka (Annals of the Polish Association of Agricultural and Agribusiness Economists)
This study aimed to identify the key factors influencing the development of energy cooperatives in Poland and assess their impact within the framework of the PESTEL analysis criteria. The research was conducted through a literature review and expert opinions gathered during the National Forum of Energy Cooperatives (2023-2024). A PESTEL analysis combined with a weighted scoring method using the EFE (External Factor Evaluation) matrix was applied to evaluate the driving forces and barriers affecting the growth of energy cooperatives. The average score obtained in the EFE matrix (2.95) suggests that the analyzed factors significantly influence the development of energy cooperatives in Poland. Legal and economic factors play the most substantial roles, highlighting the necessity for legislative changes and financial support for energy cooperatives and renewable energy initiatives. Additionally, modernizing energy infrastructure is crucial for fully harnessing the potential of renewable energy sources (RES). The relatively low importance of social and environmental factors underscores the need for enhanced education and public engagement in environmental protection.